Transfer boy : perspectives on Asperger syndrome - Vuletic, Ljiljana, 1959- (Jessica Kingsley, 2005)
Transfer Boy: Perspectives on Asperger Syndrome explores what it is like to be an adolescent with Asperger Syndrome, through interviews with Teodor, a 'psychologically unusual' thirteen-year-old. In this detailed case study, Vuletic and Ferrari combine an autobiographical account with perspectives from other family members and people who know Teodor well, while simultaneously integrating psychiatric and psychological research on autism. The authors evaluate the merits and pitfalls of different interpretations of autism and address the broad psychological issues related to Asperger Syndrome - i.